STRATEGI PENGEMBANGAN AGROWISATA KEBUN BELIMBING NGRINGINREJO, KECAMATAN KALITIDU, KABUPATEN BOJONEGORO DALAM MENGHADAPI KRISIS PANDEMI COVID-19 - Ameilia Dwi Anisa; Siwi Gayatri; Joko Mariyono (Universitas Galuh, 2022)
The Covid-19 pandemic, had an impact on several sectors, agrotourism for instance. The most visible impacts are decrease in the number of visitors and limited marketing. This study aims to analyze the internal and external environment as well as analyze the strategy for developing Ngringenrejo Agrotourism toward Covid-19 pandemic crisis. This research was conducted in December 2021 - January 2022 at Starfruit Agrotourism in Ngringinrejo Village, Kalitidu District, Bojonegoro Regency. The research location was chosen purposively. This research use case study method. The method of determining respondents used snowball sampling and accidental sampling with 40 respondents. The types of data used were primary data and secondary data. The data analysis methods used were IFE and EFE matrices, SWOT matrix analysis and QSPM matrix. The results of the SWOT analysis showsed that nine alternative strategies and priority strategies were obtained based on the QSPM analysis, namely increasing the innovation of various facilities, expanding the starfruit marketing area and carrying out more active promotions through social media. The recommended strategy that can be done is to improve various facilities such as game rides, educational tours, photo spots and cafes.